Study on the Transformation of Medan City Into a Compact City (Northern Medan City) - Bintang M Purba; Cut Nuraini; Abdiyanto (International Journal of Society and Law, 2024)
The "Compact City" planning concept aims to manage urban growth in a structured and efficient manner, as well as prevent urban sprawl or irregular urban development. The city of Medan, as a big city, has not fully implemented this concept, although the rapid development of the city has caused problems such as limited land, high urbanization, declining environmental quality, and transportation challenges. This study aims to measure the potential of regional compactness in Medan based on three main factors of urban compactness: density, mixed land, and intensification. The research approach uses a combination of quantitative and qualitative methods, where quantitative analysis is used to measure the cohesiveness factor of the city with Sturgess cluster analysis tools and spatial mapping using ArcGIS 10.5, while qualitative analysis provides a more in-depth explanation of quantitative data. The results show that out of 23 villages in northern Medan, only 4 villages have the highest potential for the implementation of the compact city concept, namely Besar Village, Tangkahan, Tanah Enam Ratus, and Rengas Pulau. This is influenced by the more formed cohesive structure, especially in the function of the mixture.